Bone Marrow Infiltration Is a Distinctive Risk Factor for Rituximab Infusion-Related Reactions in CD20-Positive B-Cell Non-Hodgkin Lymphoma - Shinya Ohata; Kei Takenaka; Daisuke Sugiyama; Takeshi Sugimoto (Advances in Hematology)
Background. Bone marrow infiltration of lymphoma cells is a candidate risk factor for infusion-related reactions (IRRs) in patients with CD20-positive B-cell non-Hodgkin lymphoma (B-NHL). However, despite with the lack of sufficient data, the effect of bone marrow infiltration of B-NHL cells on the incidence rate of grade 2 or higher IRRs with the administration of rituximab has been retrospectively studied in this paper. Methods. Patients with CD20-positive B-NHL who received the rituximab induction therapy for the first time were enrolled in this study. To evaluate the bone marrow infiltration of B-NHL cells, May–Giemsa stain of bone marrow films and flow cytometry examination of bone marrow aspiration samples were performed. IRR grade was determined using the IRR criteria in the Common Terminology Criteria for Adverse Events version 4.0. Results. A total of 127 patients were eligible for this study. Grade 2 or higher IRRs were observed in 43 (34%) patients. In univariate analysis, use of glucocorticoid before rituximab infusion was a strong risk-avoiding factor for grade 2 or higher IRRs. Advanced stage of disease (Ann Arbor: stages III and IV) or bone marrow infiltration of B-NHL cells revealed the risk factors, regardless of glucocorticoid premedication. Using multivariate analysis, bone marrow infiltration was found to be an independent risk factor for patients without prior glucocorticoid use. Conclusion. Bone marrow infiltration of B-NHL cells is a risk factor for grade 2 or higher IRRs at the first rituximab induction therapy without glucocorticoid premedication.